Selective responses of enzymes in the two parallel pathways of rosmarinic acid biosynthetic pathway to elicitors in Salvia miltiorrhiza hairy root cultures - Zhang, Shuncang; Yan, Yan; Wang, Bangqing; Liang, Zongsuo; Liu, Yan; Liu, Fenghua; Qi, Zhihong (Journal of bioscience and bioengineering, 2014)
Rosmarinic acid and salvianolic acid B are two important phenolic compounds with therapeutic properties in Salvia miltiorrhiza Bunge. The biosynthesis of rosmarinic acid is initiated by two parallel pathways, namely the phenylpropanoid pathway and the tyrosine-derived pathway. Salvianolic acid B is a structural dimer of rosmarinic acid and is believed to be derived from rosmarinic acid. In the current study, methyl jasmonate (MeJA) and hyphal extracts from fungi were used as elicitors to examine the relationship between enzymes in the two parallel pathways and accumulation of phenolic compounds in S. miltiorrhiza hairy root cultures. The results showed that accumulations of rosmarinic acid, salvianolic acid B and total phenolics were enhanced by MeJA while suppressed by fugal extracts. Responses of enzymes in the tyrosine-derived pathway, at both the gene transcript and enzyme activity levels, showed a better consistency with alterations of phenolic compounds content after the two elicitors treated. Our study implied that compared with enzymes in the phenylpropanoid pathway, enzymes in the tyrosine-derived pathway are more correlated to rosmarinic acid and salvianolic acid B biosynthesis in S. miltiorrhiza hairy roots.